Functional α-Cyanostilbenes: Sensing to Imaging - Dahiwadkar, Rahul; Kaloo, Masood A.; Kanvah, Sriram (Synlett, 2023)
In recent years, there has been considerable interest in cyanostilbenes due to their unique photophysical properties. The compounds emit light when aggregating, commonly called aggregation-induced emission (AIE). This remarkable feature makes cyanostilbenes ideal for various sensing applications, especially in aqueous environments. The detection of various analytes, such as metal ions and nitroaromatic compounds, has been accomplished using these compounds through various sensing mechanisms from chelation-enhanced fluorescence to fluorescence quenching. Furthermore, cyanostilbenes have shown great promise in biological imaging applications and have been employed for intracellular imaging, tracking, and targeting of sub-cellular organelles. The development and utilization of cyanostilbenes can significantly impact advanced sensing and imaging technologies in both analytical and biological fields. This potential stems from the unique properties of cyanostilbenes, such as their AIE characteristics, which sets them apart from other compounds and makes them highly useful for various applications. Further exploration and development of cyanostilbenes could lead to the creation of novel sensing and imaging technologies with wide-ranging applications in both academic and industrial settings.
Keywords: aggregation-induced emission; acrylonitriles; bioimaging; cyanostyrenes; chromophores